Hospital safety climate from nurses' perspective in four European countries - Gurková, E; Zeleníková, R; Friganovic, A; Uchmanowicz, I; Jarošová, D; Papastavrou, E; Žiaková, K (International nursing review, 2020)
BACKGROUND: Nursing shortages, the substitution of practical nurses for registered nurses, an ageing workforce, the decreasing number of nurse graduates and the increasing migration of young nurses are important factors associated with the hospital safety climate in Central European countries. AIMS: The aim of the study was to investigate nurses' perceptions of the safety climate in four selected central European countries (Croatia, the Czech Republic, Poland and Slovakia) and to determine the relationship between safety climate and unfinished nursing care. METHODS: A cross-sectional study was used. The sample consisted of 1353 European nurses from four countries. Instruments used were the Hospital Survey on Patient Safety Culture and the Perceived Implicit Rationing of Nursing Care. Data were analysed using descriptive statistics and multiple regression analyses. RESULTS: Significant differences were found between countries in all unit/hospital/outcome dimensions. 'Perceived Patient Safety' and 'Reporting of Incident Data' were associated with aspects of 'Organizational Learning' and 'Feedback and Communication about Error'. Higher prevalence of unfinished nursing care is associated with more negative perceptions of patient safety climate. CONCLUSIONS: Cross-cultural comparisons allow us to examine differences and similarities in safety dimensions across countries. The areas with potential for initiating strategies for improvement in all four countries are 'Staffing', 'Non-punitive Response to Error' and 'Teamwork across Hospital Units'. IMPLICATIONS FOR NURSING AND HEALTH POLICY: 'Feedback and Communicating about Error' and 'Organizational Learning - Continuous Improvement' were the main predictors of 'Overall Perception of Patient Safety' and 'Reporting of Incident Data'. Therefore, nurse managers should focus on how to empower nurses in these areas in order to foster a no-blame culture and effective reporting. In addition, it is important for policymakers to update nursing education standards in order to address patient safety.
Keywords: dospělí; Female; postoj zdravotnického personálu; Adult; ženské pohlaví; Patient Safety; průřezové studie; Organizational Culture; Slovakia; lidé; Safety Management; bezpečnost pacientů; Attitude of Health Personnel; Humans; personál sesterský nemocniční; Cross-Sectional Studies; Male; Nurse's Role; Croatia; Czech Republic; Nurse Administrators; Chorvatsko; Nursing Staff, Hospital; zdravotní sestry v řízení a kontrole; Česká republika; lidé středního věku; role ošetřovatelky; Slovenská republika; mužské pohlaví; Poland; Middle Aged; řízení bezpečnosti; organizační kultura; Polsko